(untitled) - Vernick, Audrey; 1975-; Cordell, Matthew (Clarion Books, Houghton Mifflin Harcourt, 2017)
Missing the familiarity of first grade and imagining the impossible tasks assigned by his next teacher, a boy refuses to start second grade.
Accelerated Reader AR